Examining the Socio-Economic Challenges Faced by the Elderly in Kirombe Lira City West - Rebecca Mildred Apio (Uganda Christian University, 2024)
The purpose of the study was to examine the socio-economic challenges faced by the elderly in Kirombe, Lira City West, Northern Uganda. The research study’s objectives were aimed at assessing the social challenges faced by the elderly: the economic challenges they face and whether there are any stakeholders' efforts in addressing these socioeconomic challenges faced by the elderly in Kirombe, Lira City West. The study employed both qualitative and quantitative methods of data collection. A quantitative method was used during the questionnaire approach which analyzed the numerical data of the elderly on age, household number, and percentage of health care access. A qualitative data collection method was used to collect non-numerical data through descriptive interviews with the Community Development Officer. According to a population sample N= 18 respondents, On Gender distribution 61.1% of the respondents were men and 38.9% were women. Data collected revealed that the elderly in Kirombe faced significant challenges, The social challenges included, lack of social interaction which was at 16.7%, limited mobility which was at 33.3%, lack of recreation facility was at 5.6%, poor health at 38.9% and others(discrimination, stigma ) Economically, the elderly suffer from Insufficient income which was at 44.4%, high medical expense was at 33.3%, debt was at 11.1% and others (dependence of family, high cost of living) at 11.1%. Furthermore, in the stakeholders’ efforts to address the socioeconomic challenges faced by the elderly in Kirombe Lira City West, Local Council leaders, and community development officers, allocate funds through programs like Social Assistance Grant for Empowerment (SAGE), Parish Development Model (PDM) and the Local Council Leaders participated in mobilizing older persons to benefit from these social protection programs.